Mouse Models of Experimental Autoimmune Uveitis: Comparative Analysis of Adjuvant-Induced vs Spontaneous Models of Uveitis - Chen, J.; Qian, H.; Horai, R.; Chan, C.-C.; Caspi, R.R. (Current Molecular Medicine, 2015)
Mouse models of experimental autoimmune uveitis (EAU) mimic unique features of human uveitis, and serve as a template for preclinical study. The “classical” EAU model is induced by active immunization of mice with the retinal protein IRBP in adjuvant, and has proved to be a useful tool to study basic mechanisms and novel therapy in human uveitis. Several spontaneous models of uveitis induced by autoreactive T cells targeting on IRBP have been recently developed in IRBP specific TCR transgenic mice (R161H) and in AIRE-/- mice. The “classical” immunizationinduced EAU exhibits acute ocular inflammation with two distinct patterns: (i) severe monophasic form with extensive destruction of the retina and rapid loss of visual function, and (ii) lower grade form with an acute onset followed by a prolonged chronic phase of disease. The spontaneous models of uveitis in R161H and AIRE-/- mice have a gradual onset and develop chronic ocular inflammation that ultimately leads to retinal degeneration, along with a progressive decline of visual signal. The adjuvant-dependent model and adjuvantfree spontaneous models represent distinct aspects and/or various forms of human uveitis. This review will discuss and compare clinical manifestations, pathology as well as visual function of the retina in the different models of uveitis, as measured by fundus imaging and histology, optical coherence tomography (OCT) and electroretinography (ERG).
Keywords: uveitis